1998
DOI: 10.1177/107110079801901204
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Consequences of Plantar Fascial Release or Rupture During Gait: Part I - Disruptions in Longitudinal Arch Conformation

Abstract: To examine whether conformational changes induced by plantar fascial division may progress during gait, we loaded the feet of seven cadavers using an apparatus that simulates the actions of the extrinsic plantarflexors. We measured the effects of plantar fasciotomy at two instants in the terminal-stance phase of gait. Radiographic measurements of height of the arch, base length of the arch, and talo first-metatarsal angle were used to assess contributions to arch support made by the plantar fascia, tibialis po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(28 citation statements)
references
References 28 publications
1
26
0
1
Order By: Relevance
“…Structural competency of the longitudinal arch is therefore critical in humans. Indeed, clinical work has outlined numerous risk factors associated with the surgical release of the plantar aponeurosis, including a decrease in arch height (Kim and Voloshin, 1995;Kitaoka et al, 1997;Sharkey et al, 1998) and altered stress distributions in hard (i.e., calcaneocuboid joint and metatarsals) and soft (i.e., spring ligament, short plantar ligament, long plantar ligament, flexor digitorum longus, and flexor hallucis longus) tissues (Murphy et al, 1998;Gefen, 2002;Crary et al, 2003;. A well-developed human plantar aponeurosis contributes to propulsion by rapidly transmitting forces from the hind foot to the forefoot via elastic recoil of the ''preloading'' and peakloading phases (Hicks, 1954;Wright and Rennels, 1964;Bojsen-Møller, 1979;Ker et al, 1987;Simkin and Leichter, 1990;Pataky et al, 2008;Caravaggi et al, 2009).…”
Section: Uniqueness Of the Human Ccj?mentioning
confidence: 99%
“…Structural competency of the longitudinal arch is therefore critical in humans. Indeed, clinical work has outlined numerous risk factors associated with the surgical release of the plantar aponeurosis, including a decrease in arch height (Kim and Voloshin, 1995;Kitaoka et al, 1997;Sharkey et al, 1998) and altered stress distributions in hard (i.e., calcaneocuboid joint and metatarsals) and soft (i.e., spring ligament, short plantar ligament, long plantar ligament, flexor digitorum longus, and flexor hallucis longus) tissues (Murphy et al, 1998;Gefen, 2002;Crary et al, 2003;. A well-developed human plantar aponeurosis contributes to propulsion by rapidly transmitting forces from the hind foot to the forefoot via elastic recoil of the ''preloading'' and peakloading phases (Hicks, 1954;Wright and Rennels, 1964;Bojsen-Møller, 1979;Ker et al, 1987;Simkin and Leichter, 1990;Pataky et al, 2008;Caravaggi et al, 2009).…”
Section: Uniqueness Of the Human Ccj?mentioning
confidence: 99%
“…Significant collapse of the arch in the sagittal plane was reported by Sharkey, et al [22] with a complete fasciotomy. Sharkey, et al [22] also in a follow up study found that cutting only the medial half of the plantar fascia did significantly increase peak pressure under the metatarsal heads with little effect on pressures in other regions of the forefoot or second metatarsal strain and loading. Significant shifts in plantar pressure and force from the toes to beneath the metatarsal heads and increased strain and bending in the second metatarsal caused by dividing the entire planter fascia.…”
Section: Resultsmentioning
confidence: 87%
“…Weakness of the medial longitudinal arch and pain in the lateral midfoot in cadaver specimens with a total release was repored [21]. Significant collapse of the arch in the sagittal plane was reported by Sharkey, et al [22] with a complete fasciotomy. Sharkey, et al [22] also in a follow up study found that cutting only the medial half of the plantar fascia did significantly increase peak pressure under the metatarsal heads with little effect on pressures in other regions of the forefoot or second metatarsal strain and loading.…”
Section: Resultsmentioning
confidence: 99%
“…En effet, cette section, partielle ou complète du fascia plantaire, conduirait progressivement à un pied plat, même avec une section limitée selon Sharkey et al [15]. Le fait de sectionner le fascia entraînerait une modification de conformation de l'arche plantaire.…”
Section: Discussionunclassified